2016
DOI: 10.1007/s00066-016-0995-7
|View full text |Cite
|
Sign up to set email alerts
|

The field size matters: low dose external beam radiotherapy for thumb carpometacarpal osteoarthritis

Abstract: The purpose of this work was to evaluate the efficacy of low-dose radiotherapy (RT) for thumb carpometacarpal osteoarthritis (rhizarthrosis). The responses of 84 patients (n = 101 joints) were analyzed 3 months after therapy (n = 65) and at 12 months (n = 27). Patients were treated with 6 fractions of 1 Gy, two times a week, with a linear accelerator. At the end of therapy, about 70 % of patients reported a response (partial remission or complete remission), 3 months later about 60 %, and 1 year after treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 21 publications
(15 reference statements)
0
16
0
Order By: Relevance
“…These studies had heterogeneous study populations including a variety of benign diseases and using poorly defined outcome measures. Other clinical studies did report beneficial effects of LDRT on pain and functioning 24,46 . However, these studies had inferior study designs (e.g., no control-arm, non-validated outcome measures, poorly defined study population), with high risk of bias.…”
Section: Discussionmentioning
confidence: 99%
“…These studies had heterogeneous study populations including a variety of benign diseases and using poorly defined outcome measures. Other clinical studies did report beneficial effects of LDRT on pain and functioning 24,46 . However, these studies had inferior study designs (e.g., no control-arm, non-validated outcome measures, poorly defined study population), with high risk of bias.…”
Section: Discussionmentioning
confidence: 99%
“…We suppose a response to therapy of about 70% [5,7] for both investigated treatments. The sample size calculations revealed a necessary minimum study population of 61 patients to be recruited for each therapy for a p-value pf 0.05 and 80% power, respectively (analysis with GPower 3.1 according to Faul [9].…”
Section: Study Typementioning
confidence: 99%
“…In Germany and Central Europe low-dose external beam radiotherapy (LD-EBRT) for painful degenerative diseases of the joints and tendons is widely adopted [6]. It has been established in the therapy of painful CMC arthrosis, too [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scientific background to support therapeutic management of patient with TCMC-OA exists at various levels of evidence. The traditional mainstay for conservative therapeutic management includes orthotic support (Hermann et al, 2014), pharmacological approach (Joshi, 2005;Salini, De Amicis, Abate, Natale, & Di Iorio, 2009), patient education (Stamm et al, 2002), therapeutic exercise (Valdes & von der Heyde, 2012), joint (Villafañe, Silva, & Fernandez-Carnero, 2012) and neural (Villafañe, Silva, & Fernandez-Carnero, 2011) mobilization, or radiotherapy (Kaltenborn, Bulling, Nitsche, Carl, & Hermann, 2016) among others, both isolated or in combination (Deveza et al, 2017). Although a number of them have shown to be effective, most of existing trials on TCMC-OA have demonstrated poor consistent case definition, sparse standardized outcome measures, and inadequate powering, thereby limiting their generalizability to clinical scenarios (Spaans et al, 2015).…”
Section: Introductionmentioning
confidence: 99%